Understanding the Links between System Quality, Information Quality, Service Quality, and User Satisfaction in the Context of Online Learning - Nuryanti, Yulis; Hutagalung, Dhaniel; Nadeak, Multi; Abadiyah, Siti; Novitasari, Dewiana (International Journal of Social and Management Studies, 2021)
This study aims to determine and analyze the effect of system quality, information quality, service quality on user satisfaction of online learning systems at a private university in Tangerang. The number of research samples was 429 students. The sampling technique used is simple random sampling. The analytical method used is SEM with the help of SmartPLS 3.0 software. The results showed that system quality, information quality, and service quality had a significant effect on user satisfaction of e-learning systems. The better the perception of system quality, information quality, and service quality, the more user satisfaction will increase.